Development of Emulation Network Analyzer Tool for Computer Network Planning - Mohd Nazri Ismail; Abdullah Mohd Zin (Bulletin of Electrical Engineering and Informatics, 2016)
This paper describes the development of Emulation Network Analyzer (ENA) for heterogeneous services in campus environment. The purpose of this paper is to inform this ENA able to plan and predict network performance. For this purpose, our ENA development is differ from others system such as application and hardware network analyzer. This study focuses on the design of emulation network analyzer, user interface design, characteristics, model description, implementation and evaluation. This ENA can provide a useful network architectural solutions and optimization of network resources during preparation, proposal and planning phases. Finally, ENA tool is a good emulation analyzer that can be used in small to medium size networks for campus environment purposes with minimum cost.